Determinants of energy efficiency and energy consumption of Eastern Europe post-communist economies. Issue 8 (December 2017) - Sineviciene, Lina; Sotnyk, Iryna; Kubatko, Oleksandr
Energy consumption reduction and energy efficiency improvement are recognized as global priorities in the context of the green economy and sustainable development. In this paper, determinants of energy efficiency and energy consumption for the panel of 11 post-communist countries in the Eastern Europe during 1996–2013 are investigated. The stochastic frontier function approach and comparative analysis were used to examine long-run dynamic relations. The research results show that GDP growth is a key factor increasing both energy efficiency and energy consumption. The research results on energy efficiency relations show that CO2 emissions per capita, a fixed capital and the share of industry in the economy are other important drives. In the context of per capita energy consumption growth, the factors of structural changes determined by industry share in the national economy and innovation concerned with development and implementation of high technologies are significant. The European Union accession and participation in the European energy policy promote to energy efficiency improvements in the post-communist countries while progress in governance and enterprise restructuring as measured by the European Bank for Reconstruction and Development is not important for energy efficiency and per capita energy consumption in the post-communist countries. According to the research results, energy efficiency policy in the sample countries should be aimed at providing further economic growth enhancing a positive impact of other factors and implementing energy efficiency projects.